Widespread Influence of 3′-End Structures on Mammalian mRNA Processing and Stability - Wu, Xuebing (Cell, 2017)
The physiological relevance of structures within mammalian mRNAs has been elusive, as these mRNAs are less folded in cells than in vitro and have predicted secondary structures no more stable than those of random sequences. Here, we investigate possibility that mRNA structures facilitate the 3′-end processing of thousands of human mRNAs by juxtaposing poly(A) signals (PASs) and cleavage sites that are otherwise too far apart. We find that RNA structures are predicted to be more prevalent within these extended 3′-end regions than within PAS-upstream regions, and indeed are substantially more folded within cells, as determined by intracellular probing. Analyses of thousands of ectopically expressed variants demonstrate that this folding both enhances processing and increases mRNA metabolic stability. Even folds with predicted stabilities resembling those of random sequences can enhance processing. Structure-controlled processing can also regulate neighboring gene expression. Thus, RNA structure has widespread roles in mammalian mRNA biogenesis and metabolism.